(untitled) (The Review of Diabetic Studies, 2025)
Diabetic foot ulcer (DFU) is a complication of diabetes and is associated with microbial infections. Early identification of causative microorganisms and their resistance patterns is critical for effective management. This study aimed to identify bacterial profiles in DFU patients and sought to characterize the isolated bacteria. A cross-sectional study was involving 110 DFU patients. Wound specimens were aseptically collected and cultured. Microbial identification and antibacterial susceptibility were performed. Extended-spectrum β-lactamase (ESBL)-producing strains and Methicillin-resistant Staphylococcus aureus (MRSA) were identified. Results showed the majority of DFU patients were males aged 51-60 years, with most residing in urban areas. Bacterial infections were predominant, with Gram-negative bacteria accounting for 66.67% of isolates. The most common pathogens were Pseudomonas aeruginosa and Klebsiella pneumoniae, while Staphylococcus aureus was the most frequent Gram-positive isolate. Biochemical tests supported differentiation of isolates. Antibiotic resistance was common, particularly among Gram-negative isolates, with Klebsiella pneumoniae and Acinetobacter baumannii showing multidrug resistance. Among Gram-positive bacteria, all isolates were resistant to erythromycin but remained sensitive to vancomycin, teicoplanin, and linezolid. ESBL production was highest in Klebsiella pneumoniae, and all Staphylococcus aureus and Staphylococcus haemolyticus isolates showed cefoxitin resistance. The study highlights a high prevalence of multidrug-resistant bacterial infections in DFUs, particularly among Gram-negative isolates. The frequent detection of ESBL-producing strains and MRSA underscores the urgent need for routine microbial identification and antibiotic susceptibility testing to guide effective treatment. These findings support the importance of targeted antibacterial treatment and continuous surveillance to reduce complications and improve clinical outcomes in DFU patients.